Sexual Satisfaction of Women Accepting Tubectomy and Hormonal Contraception - Hanifah, Astin Nur; Anggraini, Arie; Rahmawati, Eka; Dewi, Bela Purnama; Dewi, Chitra; Nurlaeli, Nurlaeli; Treasa, Adisty Dwi; Wahyuni, Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
In Islamic legal analysis regarding the use of contraception, the majority of ulama allow the use of contraceptives as long as they are not installed permanently, and for permanent contraceptives (vasectomies / tubectomies) the majority of ulama prohibit it. Sexual satisfaction is a form of sexual closeness felt by husband and wife couples in the interpersonal area, namely in the quality of sexual communication, attitudes towards sexual relations and balance in sexual relations. This research design uses a cross sectional study design which aims to analyze the comparative level of sexual satisfaction of women who accept tubectomy and hormonal contraception. The results of this study show that knowledge is related to the level of sexual satisfaction in women with tubectomy acceptors, while there are 2 variables that are related to the level of sexual satisfaction in women with hormonal contraception, namely knowledge with and duration of use.